Double scattering in deuteron electrodisintegration - Werner U. Boeglin; Misak M. Sargsian (Physics Letters B, 2024)
We demonstrate that at sufficiently high energies when the eikonal regime is established for hadronic interactions, the double scattering subprocess can be clearly identified and isolated in quasi-elastic deuteron electro-disintegration processes. Comparing theoretical calculations with the recent high precision experimental data we present a “proof of principle” that these processes can be used to study advanced issues related to hadron formation in QCD. In this case, the double scattering represents as a fermi-scale “detector” which probes products of high Q2 scattering from the bound nucleon through their rescattering from the spectator nucleon in the deuteron.